A bioaccessible fraction of parboiled germinated brown rice exhibits a higher anti-inflammatory activity than that of brown rice. Issue 5 (13th May 2015) - Tuntipopipat, Siriporn; Muangnoi, Chawanphat; Thiyajai, Parunya; Srichamnong, Warangkana; Charoenkiatkul, Somsri; Praengam, Kemika
<x xml:space="preserve">Abstract</x> Parboiled germinated brown rice (PGBR) has been suggested as a functional food because it is relatively rich in a number of nutrients and health promoting compounds.